Effect of medium solvents on crystalline degree and specific surface area of Cu3BiS3nanoparticles synthesised by biomolecule-assisted hydrothermal and solvothermal methods - K. Aup-Ngoen (2018)
Copyright © 2017 Inderscience Enterprises Ltd. Cu3BiS3nanoparticles were successfully synthesised by hydrothermal and solvothermal methods using L-cysteine biomolecules as a sulphur source and complexing agent. Phase and purity of the samples were characterised by X-ray diffraction (XRD) and selected area electron diffraction (SAED). Scanning and transmission electron microscopy (SEM and TEM) revealed the increasing of particle size from 29.8 ± 6.3 nm to 89.6 ± 17.2 nm by changing the medium solvents from de-ionised (DI) water to ethylenediamine (EN), in accordance with the decrease in the BET surface area from 17.5560 ± 0.1170 m2/g for the DI particles to 4.0297 ± 0.0370 m2/g for the EN particles. The absorption spectrum of highly crystalline Cu3BiS3nanoparticles synthesised in EN was used to determine the direct energy gap (Eg) which was found to be 1.6 eV. In this research, a formation mechanism is proposed and discussed according to the experimental results.